2022
DOI: 10.1111/jam.15757
|View full text |Cite
|
Sign up to set email alerts
|

The inactivation efficacy of plasma-activated acetic acid against Salmonella Typhimurium cells and biofilm

Abstract: Howard et al., 2012). Despite a decreasing trend, salmonellosis in humans is still the second most reported bacterial disease (European Food Safety Authority, and European Centre for Disease Prevention and Control, 2015).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…[15][16][17] Under the action of an applied electric eld, high-energy electrons generated by the high electric eld bombard gas molecules to produce a large number of reactive oxygen species (such as 1 O 2 and $OH), which can break the cell wall of bacteria and cause death. Kang et al 18 inactivated Salmonella typhimurium by the discharge plasma and found that the reactive oxygen species attacks played a decisive role. Ching et al 19 and Gupta et al 20 used the discharge plasma to treat Escherichia coli in water, and found that ultraviolet light participated in the generation of the reactive oxygen species and thus contributed to the inactivation of Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Under the action of an applied electric eld, high-energy electrons generated by the high electric eld bombard gas molecules to produce a large number of reactive oxygen species (such as 1 O 2 and $OH), which can break the cell wall of bacteria and cause death. Kang et al 18 inactivated Salmonella typhimurium by the discharge plasma and found that the reactive oxygen species attacks played a decisive role. Ching et al 19 and Gupta et al 20 used the discharge plasma to treat Escherichia coli in water, and found that ultraviolet light participated in the generation of the reactive oxygen species and thus contributed to the inactivation of Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that PAOA exhibited a synergistic interaction between the organic acids and plasma, likely due to the generation of reactive oxygen species ( ROS ) ( Qian et al, 2021 ; Kang et al, 2022a ). The PAOA consist of ROS composed of hydrogen peroxide, hydroxyl radical, and ozone ( Kang et al, 2022a ) and it can induce oxidative stress to bacteria, improving the bactericidal effect of PAOA ( Theron and Lues, 2007 ; Zhou et al, 2020 ). Previous study has shown that the plasma device used in this study mainly generates reactive species such as hydrogen peroxide and ozone.…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms can contaminate chicken meat during its production, distribution, and consumption, leading to rapid food spoilage and potential foodborne illnesses ( Kang et al, 2022b ). Salmonella Typhimurium and Campylobacter jejuni are the most representative pathogens in chicken, which can cause food poisoning, such as salmonellosis and campylobacteriosis ( Lin et al, 2019 ; Hatanaka et al, 2020 ; Kang et al, 2022a ). Therefore, it is essential to develop efficient method for controlling microorganisms to ensure safe chicken meat.…”
Section: Introductionmentioning
confidence: 99%